Bacterial meningitis in solid organ transplant recipients: a population‐based prospective study. Issue 5 (October 2016) - van Veen, K.E.B.; Brouwer, M.C.; van der Ende, A.; van de Beek, D.
Abstract: Background: Solid organ transplant (SOT) recipients are at risk of infections of the central nervous system. However, the incidence and clinical course of bacterial meningitis in SOT recipients are unclear. We studied occurrence, disease course, and prognosis of bacterial meningitis in SOT recipients in the Netherlands. Methods: All patients with a medical history of solid organ transplantation were selected from our nationwide prospective cohort study on community‐acquired bacterial meningitis in patients >16 years old, performed from March 1, 2006 to October 31, 2014. Data on patient history, symptoms and signs on admission, treatment, and outcome were collected prospectively. For transplant recipients, additional information was collected retrospectively. Results: We identified 6 SOT recipients, all receiving renal transplants. The annual incidence of bacterial meningitis was 7‐fold higher (95% confidence interval [CI] 2.94–17.02, P < 0.001) for renal transplant recipients as compared with the general population (9.56 [95% CI 3.98–22.96] vs. 1.35 [95% CI 1.28–1.43] per 100, 000 patients per year). One of the 6 patients (17%) presented with the classic presentation of bacterial meningitis (fever, neck stiffness, and change in mental status). Seizures were common, occurring in 33% of patients. Streptococcus pneumoniae and Listeria monocytogenes were identified in 2 patients each, and Escherichia coli and Pseudomonas aeruginosa were both identified once. Four of 6 patients (67%) had an unfavorable functional outcome. Conclusion: Bacterial meningitis is a rare but devastating complication of solid organ transplantation. SOT recipients are at high risk for developing meningitis, and recognition of this condition may be difficult, owing to atypical clinical manifestation.